Management of Posterior Capsule Rupture Complication in Cataract Patient with High Myopia and Partial Thickness Macular Hole - Bimanda Rizki Nurhidayat; Dicky Hermawan (Vision Science and Eye Health Journal, 2022)
Introduction: To report clinical outcome after posterior capsule rupture complication in a cataract patient with partial-thickness macular hole. Case presentation: A 49-year-old woman was presented with blurred vision of the left eye two years before admission. The blurred vision increased, accompanied by eye dazzled on light exposure. There was a history of myopia on both eyes and partial-thickness macular hole in the left eye. The left eye visual acuity was 3/60 with S-7.00 correction became 5/12 no improvement with pinhole. There was a partial-thickness macular hole on the left eye in the optical coherence tomography macula. Cataract surgery was performed with intraoperative posterior capsule rupture (PCR) complication. Follow-up had been monitored from day-1 until day-60 postoperatively. Conclusions: The decision of performing cataract surgery prior to macular hole surgery is a good decision. Any intraoperative complication such as posterior capsule rupture should be followed up closely to avoid macular hole worsening. Long-term follow-up should be done to prevent the late complication after surgery.